Community, Family and Animal Conservation Sustainability in the Perspective of Normative Law and Maqasid Sharia - Syaikhu, Syaikhu; Pelu, Ibnu Elmi A.S.; Badarulzaman, Muhammad Hafiz; Ihsan, Reza Noor; Patrajaya, Rafik (El-Usrah: Jurnal Hukum Keluarga, 2024)
Animal conservation aims to preserve and breed animals to achieve the benefits of a sustainable natural ecosystemincluding community and family. One of the efforts made by the government to provide information and knowledge to the public in an attempt to minimize wildlife hunting is through the legal protection of animals, as stated in Law Number 5 of 1990 concerning the Conservation of Biological Resources and Their Ecosystems, and Government Regulation Number 13 of 1994 concerning the Hunting of Game Animals. The research method used is juridical-normative with a legislative and socio-legal approach. Then, it is linked to the policy of animal conservation, which is examined from the Maqasid Shariah perspective. The research results provided recommendations to the government in creating legislation or decision policies oriented to animals that are not yet rare. These recommendations include educating the public about rare and non-rare animal species, setting educational targets, supporting conservation efforts, and establishing animal breeding programs. Furthermore, from the perspective of Maqasid Sharia, the conservation of these animals falls under the category of daruriyah, which means that the preservation and protection of wildlife are essential for the sustainability and keeping of the Hifz al-Mal element (natural ecosystem wealth).